At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
so the substitution method states that you need to subsitute one variable for another. Lets substitue for y, how do we do this? Solve for y with ethier equation.
i don't know!
I didnt ask you a questions lol I told u to solve for y on one of those equations I wont help if you dont try
i've been sitting here for like half an hour looking through the steps on how to do it
take one of those equations and solve for y, you have done this before.
I did, but i ended up with -4y= -3x+2....and that's not right
it would be -2y=-3x+2 where did u get the 4?
also thats not finished you need to get the 2 away from the y
i have know idea and ok
3x-2y=2 you subtract 3x -2y=-3x+2 then what?
that is the original equation you divide both sides by 2 to get y by itself just like we did on that other paper
i meant -1
0.o no were at -2y=-3x+2 if you divide -2 you get y=3/2x+1
that's what i had at first, but then you said the original equation was something different
I did not and you never had that you had 3x+y=1 you still need to solve for y
now that you have solved for y uou can plug that equation in for the y in your second equation
x+2y=6 3x-2y=2 im gonna use the top one becuase its easier but x+2y=6 -x -x 2y=-x+6 /2 /2 y=(-1/2)x+3 now take the other equation solve for y and SUBSTITUTE the Y;s y=(-1/2)x+3 then solve for 3x-2y=2 -2y=-3x+2 /-2 /-2 y=(3/2)x+1 y=y (3/2)x+1 = (-1/2)x+3 (4/2)x=2 *2 *2 4x=4 x=1